The Relationship Between Well-being Levels and Mental Health Among Early Childhood Education (ECE) Teachers in Selaparang District - Nurhaliza Nurhaliza; Gunawan Gunawan; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2025)
Teacher well-being is a critical factor influencing both mental health and instructional quality. This study aims to examine the relationship between well-being levels and mental health among early childhood education (ECE) teachers in Selaparang District. A quantitative correlational research design was employed, with a sample of 68 ECE teachers selected from a population of 217 using Slovin's formula. Data were collected via well-being and mental health questionnaires, which were validated using Aiken’s V and reliability-tested with Cronbach’s Alpha. The data were analyzed using simple linear regression. The results revealed a regression coefficient of 0.591 with a significance level of p < 0.001 (p < 0.05), indicating a strong, positive, and significant relationship between well-being and mental health. These findings suggest that higher levels of perceived well-being are associated with better mental health outcomes among teachers. Furthermore, the coefficient of determination (R2) was 0.335, indicating that well-being contributes 33.5% to the mental health of ECE teachers, while other factors influence the remaining 66.5%. Consequently, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted.